Fisher's theory of interest rates and the notion of real: a critique - Éric Tymoigne (Levy Economics Institute of Bard College, 2006)
By providing five different criticisms of the notion of real rate, the paper argues that this concept, as Fisher defined it or as a definition, is not relevant to economic analysis. Following Keynes and other post-Keynesians, the article shows that the notion of real rate is microeconomically and macroeconomically unfounded. Adjusting interest rates for inflation does not protect the purchasing power of wealth, and it is impossible to do so at the macroeconomic level. In addition, an empirical interpretation of the break in the correlation between interest rates and inflation since 1953 is provided.
Keywords: E43; 330; Real Interest Rate; Fisher